Performing Plurality: Meet the Alters Vlogs on YouTube as Breeding Grounds for Epistemic Justice - Liorah Hoek; Louis van den Hengel; Inge van Nistelrooij; Alice Schippers (Tijdschrift voor Mediageschiedenis, 2024)
Social media platforms have provided people with a psychiatric label the opportunity to build communities and share their stories without relying on the mediation of therapists, publishers, or broadcasters. Among them are people who identify not as one whole self, but as a system of plural personalities, often labeled as dissociative identity disorder (DID). People with plural identities started sharing videos on YouTube as a means to convey their experiences and fight stigma. In 2009, this gave rise to a distinct sub-genre of vlogs created by people with plural identities and DID: the ‘Meet the Alters’ video, where various personalities introduce themselves to the audience. This paper traces the fifteen-year evolution of these videos in order to show how the makers of the Meet the Alters videos use YouTube’s affordances and the conventions of the vlog genre to navigate a lack of hermeneutic resources outside of psychiatric discourse and understanding, allowing them to communicate their experiences in a relatable way to a general audience. Through a close reading of the staging and performance of plurality in thirteen Meet the Alters videos, posted between 2009 and April 2024, the paper reveals key developments and particularities of this genre. The analysis highlights how plural YouTubers create their own hermeneutic resources to present their potentially unfamiliar or unruly experiences in an understandable manner to their viewers. In conversation with emerging and growing plural communities, these hermeneutic resources have been continually supplemented and refined. After fifteen years, this has resulted in a rich identity-centered discourse that enables the performance and communication of plural experiences. We argue that YouTube’s specific affordances and the generic conventions of the vlog have been crucial in the emergence and development of non-stigmatising, non-psychiatric hermeneutic resources for expressing plural experiences.